Does Policy Communication During Covid Work? - Olivier Coibion; Yuriy Gorodnichenko; Michael Weber (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using a large-scale survey of U.S. households during the Covid-19 pandemic, we study how new information about fiscal and monetary policy responses to the crisis affects households' expectations. We provide random subsets of participants in the Nielsen Homescan panel with different combinations of information about the severity of the pandemic, recent actions by the Federal Reserve, stimulus measures, as well as recommendations from health officials. This experiment allows us to assess to what extent these policy announcements alter the beliefs and spending plans of households. In short, they do not, contrary to the powerful effects they have in standard macroeconomic models.
Keywords: E31; C83; D84; J26; 330; subjective expectations; fiscal policy; monetary policy; Covid-19; surveys